PENANAMAN NILAI-NILAI KARAKTER MUHAMMADIYAH MELALUI MEDIA DOKAR (DOMINO KARAKTER) PADA ANAK-ANAK PANTI ASUHAN RIDHA KABUPATEN ENREKANG - Jabri, Umiyati; S, Putriyani; Suparman, Suparman; Khumairah, Ainun; Burhan, Muh; Ayultri, Ayultri; Nuraeni, Lia Sri (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service was carried out at the Ridha Orphanage, Kab. Enrekang with the target of orphanage children. The expected goal of this PKM activity is the children of the Ridha Orphanage can develop character in the spiritual, emotional, and intellectual fields. The method that will be used in teaching Muhammadiyah character values is divided into several stages, namely: 1) Socialization; 2) Preparation; 3) Implementation; and 4) Evaluation. In addition, the learning process is carried out by applying the following methods: 1) Observation; 2) The fun learning; 3) Picture and picture; and 4) Games. This PKM activity is the children of the Ridha Orphanage need character building activities that are carried out regularly as an effort to form a generation of Muslims who are faithful, devoted, have noble character, are capable, believe in themselves, are disciplined, responsible, love the homeland, promote and develop knowledge and skills, and charity towards the realization of a primary, just and prosperous society that is blessed by Allah SWT which is the goal of Muhammadiyah Education.Â